PERBEDAAN SKOR VISUAL ANALOG SCALE DAN OWESTRY DISABILITY INDEX SEBELUM DAN SESUDAH PENATALAKSANAAN KONSERVATIF DAN OPERATIF NYERI PUNGGUNG BAWAH SPONDILOGENIK - Tannov Romalo Siregar,* Dodik Tugasworo,* Trianggoro Budisulistyo* (NEURONA, 2016)
INTRODUCTION SPONDILOGENIC LOW BACK PAIN LBP IS THE MOST COMMON CAUSE OF DISABILITY IN WORKING AGE UNDER 45 YEARS OLD THE TREATMENT REMAINS A PROBLEM FOR DOCTORS YET THERE IS A LACK OF STUDY COMPARING DIFFERENCE IN VISUAL ANALOG SCALE VAS AND OSWESTRY DISABILITY INDEX ODI SCORES BETWEEN PRE AND POST TREATMENT ON CONSERVATIVE AND OPERATIVE MANAGEMENT IN SPONDILOGENIC LBP PATIENTS